Selective electrocatalytic CO2 reduction to acetate on polymeric Cu–L (L = pyridinic N and carbonyl group) complex core–shell microspheres. Issue 14 (28th June 2021) - Guo, Fei; Liu, Bing; Liu, Mengping; Xia, Yu; Wang, Tianlong; Hu, Wei; Fyffe, Phoebe; Tian, Lihong; Chen, Xiaobo
Abstract : Highly selective electrochemical reduction of CO2 into acetate (only acetate is produced besides H2 ) is reported with polymeric Cu–L (L = pyridinic N and carbonyl group) complex core–shell microspheres. Abstract : Low selectivity is one of the greatest challenges of an electrocatalytic CO2 reduction reaction (CO2 RR), e.g., using copper-based catalysts in water solution. Herein, we report the production of pure acetate (aside from H2 ) from a CO2 RR with a novel polymeric Cu–ligand (pyridinic N and carbonyl group) complex (p-CuL) core–shell microsphere synthesized by a facile thermal-polymerization of urea and a Cu–urea complex. The highly selective reduction of CO2 to acetate, without any detectable gas products besides H2, is enabled by the unique co-coordination of pyridinic N and CO with copper whose chemical state is between +1 and +2 and the porous 3D core that is kinetically favorable for the acetate product. The maximal faradaic efficiency of acetate of ∼64% is attained at −0.37 V vs. RHE in a 0.5 M KHCO3 electrolyte, and H2 evolution is much suppressed. In the process of the CO2 RR to acetate, the Cu(ii )–carbonyl coordination remains while Cu δ + –ligand active sites are reduced to Cu(i ). In addition, the highly selective acetate production is favored by the p-CuL core–shell microsphere for the adsorption of some important intermediates of CO2 reduction and their dimerization and further e − /h + reduction, as seen from the distinctly increased CO and –OH groups in the O K-edge X-ray absorption spectrum (XAS) of p-CuL after the CO2 RR.